Seedling growth of primed seed under drought stress in sorghum - Mohammad Omar Shihab; Jalal Hameed Hamza; William Serson; Andre Amakobo Diatta; Martin Battaglia; Maythem Al-Amery; Hail Z Rihan (مجلة بغداد للعلوم)
Drought stress is considered a limiting factor during the early growth stages of sorghum. An experiment was conducted under field conditions during the fall seasons of 2017 and 2018. The objective was to improve the growth of sorghum seedlings and their chemical properties to tolerate drought stress. Three variables were investigated: first factor cultivars (Inqath, Rabeh, and Buhoth70), second factor seed priming (primed and unprimed seed). Seeds were primed by soaking for 12 hours in a solution containing 300 mg L−1 + 70 mg L−1 of gibberellic (GA3) and salicylic (SA) acids, respectively, and third factor drought stress represented by the irrigation intervals (irrigation every 2, 4, and 6 days) through calculated quantities to deliver moisture content to the field capacity (100%) at each irrigation. A randomized complete block design with four replications was used. The results showed that cultivars varied in their ability to tolerate drought stress, and seed priming improved their performance to tolerate drought stress compared to unprimed seed in both seasons by giving the highest values of plant height, leaf area, dry seedling weight, and content of chlorophyll, carbohydrate, and proline in leaves. Reducing irrigation intervals led to an increase in the values of the traits studied, except proline content in leaves, which increased as long as irrigation intervals increased. The interaction between priming treatments and irrigation intervals was significant for most of the studied traits. It can be concluded that priming has improved seed performance's ability to tolerate drought stress compared to unprimed seed.